Hubungan Tingkat Pendidikan Penderita Tuberkulosis (TB) Dengan Kepatuhan Minum Obat Anti Tuberkulosis (OAT) Di UPT PUSKESMAS Semin II Kabupaten Gunungkidul - Antoroi, Agam Bimo; Melina, Fitria (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2025)
Background: According to a report by the World Health Organization (WHO), the number of tuberculosis patients in Indonesia ranks second highest after India. The percentage of TB patients in Indonesia is 10% of the total number of TB patients worldwide which reached 10.6 million people in 2022. The distribution of tuberculosis in Indonesia is almost in every province, one of which is the province of the Special Region of Yogyakarta. In 2022, 5,374 cases of tuberculosis were found in Yogyakarta with an estimated 10,530 cases spread across 5 districts/cities in the Yogyakarta region. Research Methods: This type of research is quantitative using an analytical survey using a cross sectional approach. The population in this study is 35 people who are Tuberculosis patients who are visiting/under treatment at the Semin 2 Health Center in January – May 2024, a sample of 35 respondents was taken using the total sampling technique, with bivariate data analysis of the Spearman Rank test Research Results: The results of the study showed that the level of education at the Semin II Health Center in Gunungkidul Regency was the highest level, namely the secondary education level of 29 (82.9%) respondents, the low level of education as many as 6 (17.1%) respondents. Adherence to taking anti-tuberculosis drugs (OAT) was high level as many as 24 (68.6%) respondents, moderate level 9 (25.7%) respondents and low level as many as 2 (5.7%) respondents. Conclusion: There was a relationship between the level of education of tuberculosis patients and compliance with taking anti-tuberculosis drugs (OAT) at the Semin II Health Center in Gunungkidul Regency with a p value of 0.002 < 0.005.